Penerapan E- Government Melalui Kebijakan Teknologi, Informasi dan Komunikasi Berbasis Website Desa di Kecamatan Lemito Kabupaten Pohuwato - Rustam Tohopi; Pebriyanto A Hulinggi (PUBLIKA : Jurnal Ilmu Administrasi Publik, 2023)
The purpose of this study is to analyze the application of a government system (e-government) based on village websites by utilizing information and communication technology to achieve government accountability, transparency, effectiveness and efficiency of village governments in Lemito District. The type of research used in this study uses a qualitative approach which has natural characteristics (natural setting) as a direct data source, because a qualitative approach can reveal various kinds of facts and conditions that occur. Data collection techniques where researchers use various types of data collection where actions are carried out, namely observation (observation), interviews (interviews), documentation and triangulation (combination). Based on the results of research analysis in Lemito District, Pohuwato Regency, the implementation of e-government has not been carried out optimally, where it has not utilized what has become the policy expectation regarding the use of technology, information and communication related to transparency, accountability, effectiveness and efficiency of village government. The village government system in Lemito District still uses a manual system for public services without taking advantage of technological developments, in this case the village website. The existence of a system that is still completely manual results in slow service and is still left behind from the current developments in achieving electronic government.